المراجعة الداخلية لنظام المعلومات المحاسبي كآلية لتدعيم نظام اليقظة الإستراتجية في المؤسسة - بوسبعين, تسعديت; حوشين, كمال (جامعة الوادي - University of Eloued, 2015)
مما لا شك فيه أن المعلومة هي أساس بناء أي إستراتجية، فالاعتماء على المعلومة المفيدة والصحيحة سيؤدي إلى إرساء دعائم إستراتجية سليمة تتميز باليقظة والذكاء التي تسمح للمؤسسة بمواجهة التهديدات واستغلال الفرص المكن أن تتاح لها في محيط تنافسي، ونظرا لكون الإستراتجية تتميز بالشمول فالحاجة إلى المعلومة من مختلف مجالات النشاط في المؤسسة ضرورية، فالمعلومة المحاسبية والمالية الناتجة عن نظام المعلومات المحاسبي هي إحداها، وضمان مصداقيتها وموثوقتها مرتبط بدرجة كبيرة بمدى فعالية وظيفة المراجعة الداخلية في المؤسسة. There is no doubt that the information is the basis for building any strategy, especially when the information is useful and right. this strategy sound is characterized by vigilance and intelligence that allows the institution to confront threats and exploit opportunities in a competitive environment. due to the fact that the strategic characterized The need of the information from different areas of activity in the organization necessary, as the case of the accounting and financial information system resulting from accounting.To ensure credibility of this information we have to effective of the internal audit function in the organization.
مقال
Keywords: المراجعة، المعلومة، المحاسبة، اليقظة، الإستراتجية.; audit, information, accounting, vigilance, strategic